Autonomous replication and addition of telomerelike sequences to DNA microinjected into Paramecium tetraurelia macronuclei. - Gilley, D (1988)
Paramecium tetraurelia can be transformed by microinjection of cloned serotype A gene sequences into the macronucleus. Transformants are detected by their ability to express serotype A surface antigen from the injected templates. After injection, the DNA is converted from a supercoiled form to a linear form by cleavage at nonrandom sites. The linear form appears to replicate autonomously as a unit-length molecule and is present in transformants at high copy number. The injected DNA is further processed by the addition of paramecium-type telomeric sequences to the termini of the linear DNA. To examine the fate of injected linear DNA molecules, plasmid pSA14SB DNA containing the A gene was cleaved into two linear pieces, a 14-kilobase (kb) piece containing the A gene and flanking sequences and a 2.2-kb piece consisting of the procaryotic vector. In transformants expressing the A gene, we observed that two linear DNA species were present which correspond to the two species injected. Both species had Paramecium telomerelike sequences added to their termini. For the 2.2-kb DNA, we show that the site of addition of the telomerelike sequences is directly at one terminus and within one nucleotide of the other terminus. These results indicate that injected procaryotic DNA is capable of autonomous replication in Paramecium macronuclei and that telomeric addition in the macronucleus does not require specific recognition sequences.